Rancangan dan Implementasi Sistem Pendukung Keputusan Pemilihan Bibit Tanaman Karet - Ariska, Dewi M.; Astuti, Indah F.; Agus, Fahrul (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
Hevea brasiliensis, commonly known as rubber plants, is a plantation commodity that holds a crucial position in the economic activities of Indonesia. At one point in history, Indonesia held a prominent position in global rubber production, surpassing the output of other nations. The initial stage in establishing a successful rubber plantation involves the careful selection of outstanding plant seeds that possess the capacity to yield substantial quantities of latex characterized by exceptional quality. CV. Eja Nursery, located in South Prangat Village, Marangkayu District, Kutai Kartanegara Regency, is recognized as one of the rubber plantations in the province of East Kalimantan. The process of seed selection at this plantation for rubber trees is now conducted manually, lacking a foundation in scientifically informed decision-making. Conversely, advancements in the realm of science and technology about decision support systems (DSS) software have permeated many sectors, including the rubber plantation industry. The objective of this study is to design and implement a DSS to select rubber plant seeds at CV. Eja Nursery. The system design employs the data flow methodology, while the system itself is implemented on a web-based platform. The present study has developed a web-based decision support system aimed at assisting the staff of CV. Eja Nursery in the selection of high-quality rubber plant seeds.